Impact of biannual treatment with fluoride varnish on tooth-surface-level caries progression in children aged 1–3 years. (October 2017) - Anderson, Maria; Dahllöf, Göran; Soares, Fernanda Cunha; Grindefjord, Margaret
Abstract: Objective: This study describes caries progression at tooth-surface level in children from 1 to 3 years of age and the impact of biannual treatment with fluoride varnish. Methods: Children who participated in a cluster-randomized controlled trial and had shown signs of dental caries were included in this study (n = 801). International Caries Detection and Assessment System (ICDAS) was used to classify dental caries. The present study compared children receiving a standard yearly intervention to children receiving the same standard preventive intervention supplemented with an application of fluoride varnish every half year. Results: The maxillary incisors were the first teeth to develop cavitation (ICDAS 3–6) and also mostly affected. Further analyses focusing on maxillary incisors buccal surfaces showed that sound surfaces had least progression and that progression to extensive decay was more common in teeth that had exhibited moderate decay. A summarizing progression index (PI) was calculated for the buccal surfaces of the maxillary incisors. Between 1 and 2 years of age PI was 26% and between 2 and 3 years of age PI was 21%. The progression on buccal incisors and on occlusal first primary molars did not differ between intervention groups (p ≤ 0, 05). Conclusion: No impact on caries progression for biannual treatment with fluoride varnish was found. Clinical significance: Using fluoride varnish as a complement to standard intervention in toddlers did not add in the prevention of dental caries or its progression. The education of parents in the use fluoride toothpaste as they start brushing the teeth of their children is essential.